2020
DOI: 10.1002/jts.22492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Narrative Exposure Therapy on Posttraumatic Stress Disorder, Depression, and Insomnia in Traumatized North Korean Refugee Youth

Abstract: Refugees affected by multiple traumatic stressors are at high risk for developing trauma‐related mental disorders, including posttraumatic stress disorder (PTSD), depression, and insomnia, which is sometimes overlooked. The present study examined the effectiveness of narrative exposure therapy (NET) on trauma‐related symptoms in a sample of North Korean refugee youth. We focused on sleep patterns in addition to changes in symptom severity for PTSD, depression, and internalizing and externalizing symptoms. Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In our study, the difference in improvement in depression, anxiety and sleep quality between the two groups was not statistically significant, which was inconsistent with some previous studies. ( Alghamdi et al., 2015 ; Park et al., 2020 ). This discrepancy might be related to differences in age characteristics of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the difference in improvement in depression, anxiety and sleep quality between the two groups was not statistically significant, which was inconsistent with some previous studies. ( Alghamdi et al., 2015 ; Park et al., 2020 ). This discrepancy might be related to differences in age characteristics of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Narrative exposure therapy (NET) has been suggested as a treatment option for traumatized young NKDs, and may also be effective for the treatment of sleep problems caused by traumatic experiences [56]. The study found clinically significant reductions in PTSD, depression, and internalizing and externalizing symptoms in the NET group, but not in the treatment-as-usual group.…”
Section: Interventions To Improve Mental Health In Nkdsmentioning
confidence: 91%
“…As shown in Supplementary Table 4, nine studies evaluating KIDNET have been conducted to date. These included five control group designs including four (Gil, 2015;Peltonen & Kangaslampi, 2019) conducted a post assessment directly after the intervention, three studies (Gil, 2015;Onyut et al, 2005;Park et al, 2020) reported a follow-up assessment between 0.5 and 3 months after the intervention, and six studies (Al-Hadethe et al, 2015;Catani et al, 2009;Hermenau et al, 2011;Onyut et al, 2005;Park et al, 2020;Ruf et al, 2010) conducted follow-up assessments 6-12 months after the intervention. The two within group post-intervention effect sizes were Hedges' g = 0.7.…”
Section: Review Of Kidnet Studiesmentioning
confidence: 99%